Peran Pemerintah dalam Bidang Administrasi Kependudukan dalam Kerangka Perlindungan Hukum Warga Negara Ditinjau dari Undang-Undang No. 23 Tahun 2006 tentang Administrasi Kependudukan - Muhimah, Uum Ummul (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
Population is part of the legal activities of state administration, where legally the government in order to carry out its obligations to carry out data collection on every citizen in order to provide protection and provide public services to every citizen. Provisions of Law No. 23 of 2006 concerning Population Administration and Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration. that the essence of population data collection is essentially an effort to create results to provide services to the community. In the form of population administration data collection, it uses a population information system to make it easier for the public to obtain demographic information. In addition, population administration is carried out by all levels of government, from the government, provincial government and district/city regional governments based on the division of affairs in accordance with the provisions of Law Number. 23 of 2014 concerning Regional Government. This study uses qualitative research methods with analysis from the perspective of government authority in the field of population administration law.